2013
DOI: 10.1001/jamapediatrics.2013.2361
|View full text |Cite
|
Sign up to set email alerts
|

School Intervention to Improve Mental Health of Students in Santiago, Chile

Abstract: isrctn.org Identifier: ISRCTN19466209.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
62
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 38 publications
6
62
2
1
Order By: Relevance
“…The effectiveness of the YoPiensoSientoActuo (“I Think, Feel, and Act”) program, a CB-based classroom intervention, was evaluated in a cluster-randomized trial with 22 schools (from a potential sampling of 85 schools) in socioeconomically poor regions in Chile (Araya et al, 2013). Trios of mental health workers who had received training and ongoing supervision from senior clinicians led the intervention groups.…”
Section: Resultsmentioning
confidence: 99%
“…The effectiveness of the YoPiensoSientoActuo (“I Think, Feel, and Act”) program, a CB-based classroom intervention, was evaluated in a cluster-randomized trial with 22 schools (from a potential sampling of 85 schools) in socioeconomically poor regions in Chile (Araya et al, 2013). Trios of mental health workers who had received training and ongoing supervision from senior clinicians led the intervention groups.…”
Section: Resultsmentioning
confidence: 99%
“…The trial showed that the intervention was not significantly better than usual care, although the program was based on evidence, had good levels of attendance, used robust methodological aspects, presented high levels of adherence, and a reasonably long follow-up period. Given these results, the authors point to the evidence of other studies showing that universal school-based interventions tend to display small to none effects on depressive symptoms [22]. …”
Section: Resultsmentioning
confidence: 78%
“…A big research project from the University of Chile and Bristol University under the direction of Araya and financed by the Wellcome Trust is being implemented as a school-based intervention to improve the mental health of low-income, secondary school students in Santiago, Chile [22]. The research group has created a program named “I think, I feel, I act”.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations